Spectral efficiency of unipolar SAC-OCDMA system considering noise effects - Hamza Mohammed Ridha, Al-Khafaji; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/